5t+7=-42

Simple and best practice solution for 5t+7=-42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5t+7=-42 equation:


Simplifying
5t + 7 = -42

Reorder the terms:
7 + 5t = -42

Solving
7 + 5t = -42

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 5t = -42 + -7

Combine like terms: 7 + -7 = 0
0 + 5t = -42 + -7
5t = -42 + -7

Combine like terms: -42 + -7 = -49
5t = -49

Divide each side by '5'.
t = -9.8

Simplifying
t = -9.8

See similar equations:

| 10x^25= | | 184/32 | | -11x(x-5)=55-11x | | 15*28+34=x | | 2(b+5)=3b+8 | | 4+2(3u-7)=-2(7u-1)+6u | | 23x=3(8x+6) | | 6a-2B=20 | | -8n+20=124 | | 58-(55-2)=x | | 3x-25=2x+115 | | 72-18=x | | K^2-15k-54=0 | | 4n^2-10=0 | | 2(36-9)=x | | Ln-3x=-1 | | 4600/8000000 | | 75-18=x | | 4r+5=2r+11 | | 3a^2-9=11 | | 2x+10+x+(3x-16)=90 | | 4r-1=2 | | 4x-1/5x | | 2x+6+2x+(4x-8)=62 | | 13*(9-6)=n | | Y=4/9x-3 | | 5u-6+5(2u+3)=-3(u+1) | | 7(2x-3)=3(3x-11) | | 4xsquared=144 | | z-4+9=6 | | -1.476-1.6a=3.6a-0.28 | | z-4+ 9= 6 |

Equations solver categories